Psychosocial experience of mothers of children with sickle cell disease in Antananarivo and Toamasina, Madagascar - Samena, Hanitriniaina S. C.; Rasamoelison, Rina J.; Razanamanana, Safidisoa N.; Robinson, Annick L. (International Journal of Research in Medical Sciences, 2022)
Background: Sickle cell disease in children can disrupt life of their mothers who are at the forefront of care. The objectives of this study were to describe the psychosocial experience of these mothers, to identify factors associated to maternal anxiety and depressive disorders. Methods: A cross-sectional study was conducted from December 2017 to February 2018 with mothers of children with sickle cell disease under the age of 15 in Antananarivo and Toamasina. The abbreviated Beck and Hamilton scales were used to assess respectively depression and anxiety. Results: Of 134 mothers surveyed, 61.2% had depression and 35.8% had anxiety. Depression significantly affected mothers with more than one child with sickle cell disease (aOR=4.31, CI- 1.12-16.58) and mothers of children hospitalized at least three times per year for vaso-occlusive crisis (aOR=13.55, CI- 1.56-117.5). Anxiety was associated with blood transfusion more than three times (aOR=9.06, CI- 2.05-40.00). Pity (74.6%) and fear of death (55.2%) were the main feelings reported. Negative occupational repercussions were reported by 48.5% of mothers, marital conflict by 15.6%, financial difficulties by 43.3%. Conclusions: A global approach focused on the child and his family would be optimal for success in the management of pediatric sickle cell disease.